Leveraging Artificial Intelligence In The Development of Interactive Learning Multimedia : A Vocational Training Initiative For Broadcasting Students At Smk Cipta Insan Mandiri Depok - Ghanistantiono Dwi H; Rr Aryanti Kristantini; Dade Maulana Machdum; Erdiek Ardhianto; Hilman Jihadi; Rezkiani (International Journal Of Community Service, 2026)
The rise of Artificial Intelligence (AI) has reshaped how the multimedia and education sectors operate. Even so, students in the broadcasting program at SMK Cipta Insan Mandiri Depok continue to struggle with several issues: they understand little about how AI can be applied in multimedia production, they are not yet skilled at building interactive learning content, and they rarely get to train with up-to-date technology. Such gaps may weaken graduates’ competitiveness in a job market that increasingly expects fluency in digital tools and AI-driven creativity. This community service activity was therefore intended to strengthen the abilities of broadcasting students at the school so that they can use AI to create interactive learning multimedia that is creative, fresh, and suited to what the digital industry actually needs. The approach taken was a structured plan delivered through workshops, hands-on practice, and close mentoring, with participants guided toward concrete results in the form of AI-based interactive learning media. The method itself was arranged in a systematic, participatory, and applied way to tackle the core problem, that is, the limited use of AI in producing interactive learning multimedia. Throughout the process, partners were actively involved at every step, from identifying needs to running the training and mentoring and finally evaluating the results. The material covered the basic ideas behind AI, an introduction to an AI tool (NotebookLM), techniques for producing AI-based multimedia, and the development of interactive learning media. Eighteen students took part in the session, which ran on May 19, 2026. Afterward, participants showed a clear improvement in grasping AI concepts and in their practical ability to create AI-based multimedia content. The post-activity questionnaires showed that 95.7% of participants were satisfied with the program, 31.9% strongly agreeing and 63.8% agreeing that the training lived up to their expectations. The program also yielded a relevant AI-based training module built with NotebookLM along with interactive learning products, which supports the longer-term goal of raising education quality in the digital era.